Efektivitas Penggunaan Media Geogebra Ditinjau Dari Pemahaman Konsep Matematis Siswa Pada Materi Dimensi 3 - Julita, Julita; Sucipto, Lalu; Nasrullah, Ahmad (Mathematic Education Departement, State Islamic University of Mataram, 2022)
The purpose of this study is to determine the effectiveness of the use of GeoGebra media in terms of understanding students' mathematical concepts in dimension 3 material. This research is a type of quasi-experimental research with a quantitative approach. The research design used is a type of nonequivalent control group design. This research took place at the Abhariyah Islamic High School, West Lombok. The population in this study were students of class X high school. The sample of researchers took all the students of class X sma with a total of 30 students, of which 15 students were used as experimental classes and 15 students in the control class. The instrument used in this study is a test. Hypothesis tests were carried out using an independent samples t test. The results showed that the use of GeoGebra media can help students in understanding mathematical concepts (effectively). With the calculation results obtained are as follows: the average Post-Test of the experiment and control classes is 13.6 and 12.4. With a significant degree of α = 5% = 0.05, db = n – 2 = 30 – 2 = 28. So that t_tabel=t_((0,025;28) )=2,048 with t_hitung=2,738. Post-Test experiment and control classes show that t_hitung>t_tabel then H_0 rejected. So, it can be concluded that post-test experimentation and control have differences. Based on the calculation results of the N-Gain Score test, it shows that the average value of the N-Gain Score for the experimental class is 72.7944 or 73% belonging to the category of quite effective. With a minimum N-Gain Score of 58.14% and a maximum of 88%. And it can be concluded that this means the effective use of GeoGebra media in terms of understanding students' mathematical concepts in dimension 3 material.